A comparison between different anti-retroviral therapy regimes on soluble inflammation markers: a pilot study - Maritati, Martina (AIDS Res Ther, 2020)
BACKGROUND: Although HIV-related deaths have decreased dramatically following the introduction of antiretroviral therapy (ART), HIV infection itself causes increased morbidity and mortality for both non-AIDS-related events or chronic inflammation and immune activation. The use of certain antiretroviral drugs can contribute to this process. METHODS: We investigated 26 potential biomarkers in serum samples from HIV-1 infected patients virologically suppressed under ART. The main objective of our study was to evaluate if virological suppression achieved with a triple drug regimen containing tenofovir disoproxil fumarate co-formulated with emtricitabine (TDF/FTC) as backbone, could correlate with a better immunological and inflammatory profile in relation to the third class of antiretroviral drug administered. The eligible patients were then divided into 3 groups in relation to the third drug associated with TDF/FTC: nucleoside reverse transcriptase inhibitors (NNRTI) (Group 1, n = 16), protease inhibitors (PI) (Group 2, n = 17) and integrase inhibitors (INI) (Group 3, n = 16). RESULTS: Inflammatory cytokines and chemokines were more represented in Group 2 than in Group 3 (IL-1Ra, p = 0.013; IL-12p70 p = 0.039; TNF-α p = 0.041; IL-8, p = 0.027; MIP1 β, p = 0.033). Eotaxin showed lower levels in Group 1 compared to Group 2 (p = 0.010), while IP-10 was significantly lower in Group 1 compared to both Group 2 and Group 3 (p = 0.003 and p = 0.007, respectively). CONCLUSIONS: Our results seem to discourage the administration of PI as a third drug in a virologically effective antiretroviral regimen, as its use is linked to the detection of higher levels of pro-inflammatory mediators in comparison with INI and NNRTI.